2013
DOI: 10.1038/nrd4140
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and other non-coding RNAs as targets for anticancer drug development

Abstract: With the first cancer-targeted microRNA drug, MRX34, a liposome-based miR-34 mimic, entering phase I clinical trial in patients with advanced hepatocellular carcinoma in April 2013, miRNA therapeutics are attracting special attention from both academia and biotechnology companies. Although to date the most studied non-coding RNAs (ncRNAs) are miRNAs, the importance of long non-coding RNAs (lncRNAs) is increasingly being recognized. Here we summarize the roles of miRNAs and lncRNAs in cancer, with a focus on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
1,024
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,298 publications
(1,035 citation statements)
references
References 179 publications
(224 reference statements)
4
1,024
0
7
Order By: Relevance
“…The pre-miRNA is then exported to the cytoplasm and cleaved by Dicer into double stranded miRNAs. [24][25][26] It has been reported that Drosha associates with dozens of distinct polypeptides, including DGCR8, to form a large 'microprocessor' Drosha complex. 27 The processing of primiRNA by the Drosha complex takes place concurrently with or shortly after transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-miRNA is then exported to the cytoplasm and cleaved by Dicer into double stranded miRNAs. [24][25][26] It has been reported that Drosha associates with dozens of distinct polypeptides, including DGCR8, to form a large 'microprocessor' Drosha complex. 27 The processing of primiRNA by the Drosha complex takes place concurrently with or shortly after transcription.…”
Section: Discussionmentioning
confidence: 99%
“…As cancer‐specific miRNAs are master regulators of many critical oncogenic pathways, their utilization for cancer diagnosis and as promising potential therapeutic target for clinical treatment strategies or personalized medicine is becoming more and more clear (Ling et al ., 2013). After discovering the role of miRNAs in cell–cell signaling and TME, targeting miRNAs as anticancer therapeutic strategy is becoming more realistic and promising.…”
Section: Novel Mirna‐based Therapeutic Approachesmentioning
confidence: 99%
“…Therefore, an ideal targeted therapy should focus on many key coding and/or regulatory sequences involved in the process of carcinogenesis. A significant advantage of using miRNAs as potential targets and/or treatment agents is their ability to regulate the expression of a number of genes and non-coding sequences that are associated with a single pathway or are involved in the regulation of parallel signalling pathways that control tumour development [165]. Compared with treatment based on small interfering RNAs (siRNAs), each of which can only silence one gene, the use of miRNAs as treatment agents seems much more beneficial.…”
Section: Mirnas As Therapeutic Agents In Nsclc Treatmentmentioning
confidence: 99%